Iowa RBA, November 18, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for November 18, 1996. Highlights of the update include sightings of a Pomarine Jaeger, a Snowy Owl, Western Grebes, Long-tailed Ducks, a Thayer's Gull, and a Pacific Loon. Also included are handwritten notes for the next week's update with sightings of a White-winged Scoter, Horned Grebes, and a Scarlet Tanager. Epson - sheet feed/flatbed